Characterization of Steiner Domination with Chromatic Number in Fuzzy Graphs - G. Priscilla Pacifica, J. Jenit Ajitha (Mathematical Statistician and Engineering Applications, 2022)
If G is a connected graph and S is a subset of , then the Steiner distance is defined as the minimum size among all connected minimal sub graphs whose node sets contain S. These sub graphs are called Steiner trees of S. The Steiner interval, or , of a set S is defined by IG(S) = w ? V (G) / w lies on a Steiner tree for S in G. If I(S)=V(G) then S is called a Steiner set. This article characterizes fuzzy graphs with crisp nodes using steiner dominating number and chromatic number.